Coordination in the Labor Market - Marja-Liisa Halko; Juha Virrankoski (Aboa Centre for Economics (ACE), 2011)
We solve the equilibrium market structure in a labor market where vacancies and unemployed workers can meet either in an intermediated market where wages are determined by take-it-orleave- it offers, or in a directed search market where firms post wages. By using an intermediary agents avoid the coordination problem which prevails in the search market. We study a monopolistic intermediary and perfect competition between intermediaries, and we consider the welfare properties of an intermediary institution, compared to an economy with an uncoordinated search process only.
Keywords: D40; J41; J64; 330; intermediary; matching; labor market